Data on the circulating levels of endothelial microparticles are elevated in patients with bicuspid aortic valve and are related to aortic dilation - Alegret, Josep M. (Data Brief, 2016)
The data included here support the research article “Circulating endothelial microparticles are elevated in bicuspid aortic valve (BAV) disease and related to aortic dilation” (Alegret et al., 2016 [1]) where circulating levels of platelet endothelial cell adhesion molecule (PECAM(+)) endothelial microparticles (EMPs) were identified as a biological variable related to aortic dilation in patients with BAV disease. The data presented in this article are composed by four tables and one figure containing the clinical and echocardiographic characteristics of the patients (Alegret et al., 2016 [1]) included in this study, and summarize the results of multivariate linear analyses. Furthermore, is also included a figure showing a representative flow cytometry dot plots and histograms used in PECAM(+) EMPs quantification is also included.